Ketidakseimbangan Regulasi Dan Realitas Dalam Penegakan Hukum Pekerja Migran Indonesia - Anthon Fathanudien; Rina Susanti (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze the imbalance between regulations and reality in law enforcement against Indonesian Migrant Workers. The problem formulation in this study is the legal regulations regarding migrant worker regulations in Indonesia and the implementation of legal regulations to the reality of law enforcement for migrant workers in Indonesia. The method used is normative juridical legal research with an approach to legislation and relevant literature. The results of the study indicate that although Law Number 18 of 2017 has provided a comprehensive legal protection framework for Indonesian Migrant Workers and the implementation of legal regulations to the reality of law enforcement for migrant workers in Indonesia, its implementation still faces major challenges. The main obstacles include weak coordination between agencies, minimal supervision, and limited protection for non-procedural Indonesian Migrant Workers. In addition, legal processes for violations such as human trafficking are often hampered by difficult to obtain evidence and logistical limitations.